Analisa Operasi Paralel Permanent Magnet Synchronous Generator Dalam Sistem Konversi Energi Angin - Agusnadi Agusnadi; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The wind energy conversion system using Permanent Magnet Synchronous Generator (PMSG) has been used as a solution for applications that have low-speed initial drives such as wind turbines and micro-hydroturbines. This study aims to analyze the effect of operating a PMSG and parallel units in an isolated wind conversion system using a three-phase rectifier with diode type and boost converter with varying wind speed characteristics on wind turbines. The power capacity of the wind turbine generator is 500 Watt with an output voltage of 24 Vac and the battery energy storage system has a capacity of 50 Ah. The results of a simulation of the PMSG operating circuit in a wind energy conversion system for one unit, using a 50 ohm resistance at wind speeds of 10 m/s to 12 m/s produce a converter output voltage of 26.58 Vdc at a wind speed of 10 m / s , 39.45 Vdc at a wind speed of 11 m/s, and 52.84 Vdc at a wind speed of 12 m/s. In the operation of a wind energy conversion system for four units, each converter output voltage with a wind speed of 12 m/s is a 41.3 Vdc one turbine, 44.75 Vdc two turbines, 46.3 Vdc three turbines and four 37.57 turbines Vdc.Keywords : Renewable Energy, Wind Energy Conversion System, Permanent Magnet SynchronousGenerator, Boost Converter, Three-Phase Rectifier